Implementation of Strategies for Combating Stunting in Sanggau Regency - Fedri Fantera Rendika; Sadu Wasistiono; Baharuddin Thahir (INFOKUM, 2025)
The case of stunting is a problem that is of concern to us considering that the growth and development of children at this time illustrates or produces what Indonesian human resources will be like in the future. Therefore, this stunting case must be resolved so that Indonesia has quality human resources to be able to compete in the era of technology and in terms of the quality of its mental and physical growth and development. This study aims to determine/analyze strategies in overcoming stunting in Sanggau Regency and analyze the inhibiting factors and supporting factors of strategies in overcoming stunting in Sanggau Regency. This study uses a qualitative research design and descriptive method, by adapting the SOAR Analysis model proposed by Stavros 2009. The results of these four dimensions are 1) Strength has been categorized as quite ready. 2) Opportunity has utilized everything effectively and efficiently. 3) Aspiration is categorized as having made efforts to achieve the readiness target. 4) Result/Result The government has implemented efforts so that the target is achieved. Furthermore, the supporting factors of the Sanggau Regency Government have implemented efforts in overcoming Stunting cases in Sanggau Regency such as vertical coordination between the Central Government and the Regional Government, issuing regulatory policies on overcoming stunting, programs and activities related to stunting, budget preparation, development of health infrastructure facilities and infrastructure. Furthermore, the inhibiting factor is data collection using two models, namely EPPBGM and SSGI. Data from EPPBGM is the overall result, while data collection from SSGI is the result of community attendance/participation at Posyandu.